How economic growth reduces poverty: A general equilibrium analysis for Indonesia - George Fane; Peter Warr (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
Do changes in poverty and inequality depend directly on the rate of economic growth, or does the source of the growth also matter? This paper uses a computable general equilibrium model of the Indonesian economy to explore this question by simulating increases in GDP arising from (i) technical progress in each of seven broad sectors, and (ii) the accumulation of each of six types of physical and human capital. The more a given amount of growth raises the returns to the factors that are more important sources of income for the poor than for the non-poor, the more it reduces poverty and inequality. Different sources of growth affect poverty and inequality differently because they affect factor returns differently, and because the poor and the non-poor own factors in different proportions. – poverty ; inequality ; growth ; Indonesia
Keywords: D58; I32; O53; 330; Sozialprodukt; Armut; Allgemeines Gleichgewicht; Indonesien